Application of microwave ablation in the emergent control of intraoperative life-threatening tumor hemorrhage during hepatic surgeries. (3rd October 2018) - Zhou, Haoming; Wu, Jindao; Ling, Wei; Zhu, Deming; Lu, Ling; Wang, Xuehao; Pu, Liyong; Kong, Lianbao
Abstract: Purpose: This study was designed to evaluate the efficacy and safety of microwave ablation (MWA) in the treatment of intraoperative life-threatening tumour haemorrhage during hepatic surgeries. Methods: Three cases of MWA application in the emergent control of life-threatening hepatic tumour haemorrhage were analysed and reported. Results: Satisfactory hemostasis for hepatic tumour rupture was achieved by MWA in all three cases. No major complications, such as post-operative haemorrhage, bile duct injury, liver abscess, colon perforation, skin burns, tumour seeding or renal dysfunction, were identified. Conclusions: MWA may be a feasible, effective and simple strategy for the emergent control of intraoperative hepatic tumour bleeding. To the best of our knowledge, this study represents the first reported cases of this novel application of MWA.